A longitudinal corpus investigation of grammatical stance markers in the English argumentative writing of chinese students / Deliang Man - Deliang , Man (2020)
Evaluation is considered crucial for successful academic writing (Hunston, 1989, 1994; Hyland & Jiang, 2016; G. Thompson, 2001). It conveys the values and judgement of the writer, maintains the relations between the writer and reader and organizes the discourse (G. Thompson & Hunston, 2000). Despite the importance of evaluation, the use of evaluative language in academic writing has shown to be difficult for both L1 and L2 users of English. One active strand of research in English for academic purposes gives considerable attention to the use of linguistic markers of stance. While there has been growing research interest in stance expression in L2 writing, little is known about how L2 users might go about learning to evaluate over time. Even less empirical research has investigated the development of evaluative language from a non-essentialist approach despite repeated calls for researching second language development from a bilingual perspective (Brown, 2013; Cook, 1999; Ortega, 2013, 2018a, 2018c). The general aim of the present thesis is to shed light on the developmental trajectories of evaluative language. In doing so, it examined the use of a set of grammatical stance markers (i.e., evaluative that-clauses, modals and semi-modals, and stance adverbials) in a longitudinal learner corpus, which consists of 632 argumentative essays produced by 158 Chinese undergraduates at four points in time. Frequency of the grammatical stance markers under examination were compared across the four points in time and qualitative analyses of the concordance lines were carried out. The results show that patterns of changes in the use of grammatical stance markers are complex: (1) patterns of changes vary with the linguistic structures under investigation: whereas the frequency of evaluative that-clauses has increased over time, the frequency of modals and semi-modals has decreased; (2) the trajectory for longitudinal changes is iv not linear: the frequency of grammatical stance markers changes in an organic, dynamic manner; (3) instances of innovative language use were observed in the corpus, which offer valuable insights into language development from a longitudinal perspective. This thesis shows the value of using longitudinal learner corpora for the study of L2 evaluative language development. Implications for language teaching in tertiary education are discussed.